A comparative study between the incidence and epidemiological features of Influenza-Like Illness and laboratory-confirmed COVID-19 cases in the Italian epicenter (Lombardy). Issue 5 (May 2021) - Grosso, Francesca; Castrofino, Ambra; Del Castillo, Gabriele; Galli, Cristina; Binda, Sandro; Pellegrinelli, Laura; Bubba, Laura; Cereda, Danilo; Tirani, Marcello; Gramegna, Maria; Bella, Antonino; Castaldi, Silvana; et al.
Abstract: Introduction: In Lombardy, the influenza surveillance system relies on sentinel physicians that weekly report data on the number of Influenza-Like Illness (ILI) and a part of them also collect nasopharyngeal samples for virologic analyses. This study aims at comparing the ILI incidence of 2019–2020 influenza season with the incidence of COVID-19 cases in order to better understand the current epidemic and to evaluate whether the implementation of ILI surveillance system could succeed in early detection and monitoring of COVID-19 diffusion. Methods: The distribution of ILI cases in the seasons 2017–2018, 2018–2019 and 2019–2020 was taken in consideration and the curve trends were compared and analyzed according to geographical areas, age groups and time differences. Results: The curve trends presented a similar pattern up to the 9th week; in fact, a reduction in the ILI incidence rate was observed in the 2017–2018 and 2018–2019 season but in the 2019–2020 an increase in the reported ILI emerged. The relation between the numbers reported by 2019–2020 ILI surveillance and those reported for COVID-19 is supported by the curve trends, the correspondence between age groups, the correspondence by geographical location, and also by the results of the nasopharyngeal swab tests performed. Discussion: The influenza surveillance system is an effective tool for early detection of COVID-19. It may provide timely and high-quality data evaluating the SARS-CoV-2 burden among population with ILI. Implementation of the system has to be prioritized in order to identify any future novel respiratory pathogen with pandemic potential.